2021
DOI: 10.3390/ijerph18084089
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Burden and Experiences Following Exposure to COVID-19: A Qualitative and Quantitative Study of Chinese Medical Student Volunteers

Abstract: Background: During the COVID-19 pandemic, some medical students devoted themselves to volunteer activities, but it was the first time that they had been exposed to such an infectious disease and they might have experienced fear in the face of the epidemic. We aimed to conduct a timely assessment of the psychological burden and experience on medical student volunteers during the COVID-19 pandemic. Methods: We used the 21-item Depression Anxiety Stress Scales to survey the psychology burden of students in April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Our findings are not surprising and confirmed recent studies that found that volunteers serving during the COVID-19 pandemic, although initially experiencing distress conditions, were "happy" and satisfied [57]. Compared to the few published studies on volunteer civilians, many studies have been conducted on medical students and future healthcare professionals' volunteering, reporting a sense of giving real aid among the benefits, driven by altruism and the ethical imperative to serve their community [58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are not surprising and confirmed recent studies that found that volunteers serving during the COVID-19 pandemic, although initially experiencing distress conditions, were "happy" and satisfied [57]. Compared to the few published studies on volunteer civilians, many studies have been conducted on medical students and future healthcare professionals' volunteering, reporting a sense of giving real aid among the benefits, driven by altruism and the ethical imperative to serve their community [58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 88%
“…Table 1 shows the overall characteristics of the 41 included studies ( Elhadi et al, 2020 ; Jindal et al, 2020 ; Liu et al, 2020 ; Medeiros et al, 2020 ; Muhammad Alfareed Zafar et al, 2020 ; Nadeem et al, 2020 ; Nakhostin-Ansari et al, 2020 ; Nihmath Nisha et al, 2020 ; Sartorao Filho Carlos et al, 2020 ; Sun et al, 2020 ; Adhikari et al, 2021 ; Banstola et al, 2021 ; Basheti et al, 2021 ; Bilgi et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Gupta et al, 2021 ; Halperin et al, 2021 ; Kalkan Uğurlu et al, 2021 ; Kaplan Serin and Doğan, 2021 ; Keskin, 2021 ; Kuman Tunçel et al, 2021 ; Li et al, 2021 ; Mekhemar et al, 2021 ; Meng et al, 2021 ; Nishimura et al, 2021 ; Patelarou et al, 2021 ; Pavan et al, 2021 ; Pelaccia et al, 2021 ; Perissotto et al, 2021 ; Saeed and Javed, 2021 ; Safa et al, 2021 ; Song et al, 2021 ; Xiao et al, 2021 ; Xie et al, 2021 ; Yadav et al, 2021 ; Yang et al, 2021 ; Yin et al, 2021 ; Zhang et al, 2021a ; Zheng et al, 2021 ; Zhu et al, 2021 ). On the whole, 40 cross-sectional studies and 1 longitudinal study were included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a study from China found that medical students’ experience volunteering during the pandemic had no influence on their future career choices. 44 During the 2009 swine influenza pandemic, the Royal Medical Academy of Belgium found that 91% of medical students felt that H5N1 patient care should be incorporated into the curriculum; and indeed this could be a strong consideration for the COVID-19 pandemic also. 45 Being exposed to and working in different settings is important for making informed career choices.…”
Section: Discussionmentioning
confidence: 99%